Structural insights into the HNF4 biology - Beinsteiner, Brice; Billas, Isabelle M. L.; Moras, Dino (Frontiers in Endocrinology, 2023)
Hepatocyte Nuclear Factor 4 (HNF4) is a transcription factor (TF) belonging to the nuclear receptor (NR) family that is expressed in liver, kidney, intestine and pancreas. It is a master regulator of liver-specific gene expression, in particular those genes involved in lipid transport and glucose metabolism and is crucial for the cellular differentiation during development. Dysregulation of HNF4 is linked to human diseases, such as type I diabetes (MODY1) and hemophilia. Here, we review the structures of the isolated HNF4 DNA binding domain (DBD) and ligand binding domain (LBD) and that of the multidomain receptor and compare them with the structures of other NRs. We will further discuss the biology of the HNF4α receptors from a structural perspective, in particular the effect of pathological mutations and of functionally critical post-translational modifications on the structure-function of the receptor.